EROS, c'est la vie. Issue 3 (1st April 2020) - Harris, Steven
Abstract : The Exposition inteRnatiOnale du Surréalisme, or EROS, which took place in Paris between December 1959 and February 1960, was focused on the origins of art in the erotic drives, and was oriented implicitly to its contemporary moment in regard to the censorship of political and sexual material in the Fifth Republic. The exhibition is examined in relation to issues of hybridity, encounter, ritual, and the destabilization of identities, using Nora Mitrani's definition of scandal as a mixing of categories. Robert Rauschenberg's and Jasper Johns's works in the exhibition are discussed in light of these issues, as is a photograph by William Klein of the surrealist group in the precincts of the exhibition, for the French edition of Vogue .